Pemberian Jus Jaya Mengatasi Konstipasi Pada Mahasiswa Jurusan Gizi Poltekkes Kemenkes Semarang - Novitasari, Hana; Tursilowati, Susi; Hendriyani, Heni (Jurnal Riset Gizi, 2014)
Background : Fiber intake of the Central Java population on average 51% of the level of adequacy of the fiber. Lack of fiber can cause constipation, which gives the symptoms of constipation is less convenient because of the perceived pain either before or during the process of defecation. Recent study showed that the prevalence of constipation women who worked in Jakarta was 47.6%. Good source of fiber for constipation is insoluble fiber found in fruits and vegetables, among others present in red guava, green apple, and papaya are then processed into juice. Taste test research has been conducted to test the acceptability of the juice . Then be made juices are high in fiber with 50 grams of the composition of guava, green apple 25 grams, and 25 grams of papaya is shortened to Juice Jaya.Objective: This study aimed to determine the Effect of Juice Jaya to Constipation In Level I Student of Nutrition Department of Health Polytechnic Semarang 2013/2014.Method: This study used the Approach Pre-test - Post test randomized control group design.and Anacova analize with MoH polytechnic students were 20 people who suffer from constipation .Results: First level of Nutrition Program Students have constipation is 21.55 %. Fiber intake before the study was 14.52 grams in the treatment group and was 13.53 grams in the control group. After the study, Fiber intake on the treatment group increased 20.45 grams, and relative constan in the control group 14.79 grams (p = 0.004). Incidence of constipation after the study decreased to 15.0 % in the treatment group and relative equal 50.0 % in the control group (p = 0.003) .Conclusion: There is the effect of the juice Jaya on the incidence of constipation in first level of Nutrition Departemen Students of Health Polytecnic Semarang.